Traditional Chinese Medicine ointment combined with infrared heat lamp in the treatment of systemic sclerosis and related nursing management: A case report (1 例系统性硬化症患者应用中药膏摩联合红外线烤灯治疗的护理体会) - GAO Donghua (高冬华); LI Qingling (李庆玲); QI Tiantian (齐添添); TANG Ling (唐玲) (中西医结合护理)
This paper reviewed the nursing management of a patient undergoing Traditional Chinese Medicine (TCM) ointment application combined with infrared heat lamp for systemic sclerosis. On the basis of routine care, the TCM ointment application combined with infrared-heat therapy was carried out to relieve the clinical symptoms of systemic sclerosis. The Visual Analogue Scale on pain dropped from 7 to 3, and the degree of swelling decreased form grade 2 to grade 0. The TCM ointment application combined with infrared heat lamp therapy displayed a remarkable effect in the treatment of systemic sclerosis and did not show any adverse reactions. (本文回顾1例系统性硬化症患者应用中药膏摩联合红外线烤灯治疗的护理体会。在常规护理的基础上, 给予患者中药膏摩联合红外线烤灯治疗, 以改善患者系统性硬化症症状。干预后患者疼痛、肿胀明显好转, 疼痛评分由7分降低至3分, 肿胀程度从Ⅱ级降至0级。中药膏摩联合红外线烤灯作用直接、效果明显、无不良反应, 对促进患者康复具有积极意义。)